Effect of silica fume to the strength and permeability of high performance ground granulated blastfurnace slag concrete - Ali Bashah, Azli Shah (2006)
A durable concrete is one that has the ability to withstand the damaging effects of the environment and of its service conditions without undue deterioration and excessive unforeseen maintenance over the design life of a structure. The used of high performance concrete is an alternative in producing high – strength concrete, durable and construction friendly. This paper study the effect of silica fume to the properties of high performance ground granulated blastfurnace slag concrete to reveal the potential outmost. It was found by compressive strength test, that highstrength concrete can be achieved. At the age of 28 days, concretes containing 5, 7.5, and 10% silica fume gave compressive strengths of 65.6, 64.6, and 67.1 Mpa, respectively. At aged 56 days concrete containing 10% of silica fume had the highest strength. However the concrete containing 5% of silica fume had low permeability thus may enhance the durability